Use of functional traits to assess changes in stream fish assemblages across a habitat gradient - Ribeiro, Mariela Domiciano [UNESP]; Teresa, Fabrício Barreto; Casatti, Lilian [UNESP] (FapUNIFESP (SciELO), 2016)
Functional traits are important for understanding the links between species occurrence and environmental conditions. Identifying these links makes it possible to predict changes in species composition within communities under specific environmental conditions. We used functional traits related to habitat use and trophic ecology in order to assess the changes in fish community composition between streams with varying habitat structure. The relationship between the species traits and habitat characteristics was analyzed using an RLQ ordination analysis. Although species were widely distributed in habitats with different structures, physical conditions did favor some species based on their functional characteristics. Eight functional traits were found to be associated with stream habitat structure, allowing us to identify traits that may predict the susceptibility of fish species to physical habitat degradation.
Keywords: Agroecosystem; Freshwater; Morphology; RLQ analysis; Tropical fish